2001
DOI: 10.1128/aem.67.12.5668-5674.2001
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the GRE3 Aldose Reductase Gene and Its Influence on Xylose Metabolism in Recombinant Strains of Saccharomyces cerevisiae Expressing the xylA and XKS1 Genes

Abstract: Saccharomyces cerevisiae ferments hexoses efficiently but is unable to ferment xylose. When the bacterial enzyme xylose isomerase (XI) from Thermus thermophilus was produced in S. cerevisiae, xylose utilization and ethanol formation were demonstrated. In addition, xylitol and acetate were formed. An unspecific aldose reductase (AR) capable of reducing xylose to xylitol has been identified in S. cerevisiae. The GRE3 gene, encoding the AR enzyme, was deleted in S. cerevisiae CEN.PK2-1C, yielding YUSM1009a. XI fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
111
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(118 citation statements)
references
References 38 publications
4
111
0
1
Order By: Relevance
“…XR, XDH and XK activities were measured in the reference strain CEN.PK 113-7A and in the two constructed strains TMB3265(XYL2, XKS1 ) and TMB3267(XYL2, XKS1, GRE3 ) ( Table 2). XR activity with NADPH as co-factor was 5-6 mU/mg protein in CEN.PK 113-7A and TMB3265(XYL2, XKS1 ), similar to previously reported (Kuhn et al, 1995;Träff et al, 2001), whereas no XR activity was detected with NADH as co-factor. In TMB3267, overexpressing GRE3, the XR activity with NADPH was increased four times.…”
Section: Role Of Gre3p In Xylose Fermentationsupporting
confidence: 90%
“…XR, XDH and XK activities were measured in the reference strain CEN.PK 113-7A and in the two constructed strains TMB3265(XYL2, XKS1 ) and TMB3267(XYL2, XKS1, GRE3 ) ( Table 2). XR activity with NADPH as co-factor was 5-6 mU/mg protein in CEN.PK 113-7A and TMB3265(XYL2, XKS1 ), similar to previously reported (Kuhn et al, 1995;Träff et al, 2001), whereas no XR activity was detected with NADH as co-factor. In TMB3267, overexpressing GRE3, the XR activity with NADPH was increased four times.…”
Section: Role Of Gre3p In Xylose Fermentationsupporting
confidence: 90%
“…At a specific d-xylose consumption rate of 0.73 mmol (g biomass) -1 h -1 this yeast excreted d-xylulose at a rate of 0.20 mmol (g biomass) -1 h -1 (corresponding to 30% of consumed d-xylose), which suggested that reactions downstream of d-xylulose were rate-controlling. Moreover, small amounts of xylitol were produced in these cultivations, suggesting involvement of a non-specific aldose reductase such as encoded by GRE3 [66]. This information on d-xylulose and xylitol production was used in subsequent metabolic engineering attempts to improve the d-xylose consumption rate and to minimise xylitol formation.…”
Section: Characterisation Of Yeast Strains With High-level Functionalmentioning
confidence: 99%
“…E2 XylA gene [43]. Since the non-specific aldose reductase encoded by GRE3 had previously been implicated in xylitol formation by S. cerevisiae, this gene was also deleted in the engineered strain [45,66].…”
Section: Metabolic Engineering For Improved Xylose-isomerase Based D-mentioning
confidence: 99%
See 1 more Smart Citation
“…Expressing the XI pathway can avoid the cofactor imbalance problem under anaerobic conditions, but xylitol accumulation has also been observed in strains expressing XI (17,18,20), because the nonspecific aldose reductase encoded by the GRE3 gene can produce xylitol from xylose (27). Various rational approaches have been used to reduce xylitol accumulation and improve xylose utilization, such as optimizing the expression levels of xylose-assimilating reactions (26), engineering the cofactor preference of XR/XDH enzymes (28)(29)(30)(31)(32)(33), perturbing the pentose phosphate pathway by gene knockout or overexpression (34)(35)(36)(37)(38)(39), or deleting GRE3 in strains expressing the XI pathway (21,40,41). While extensive previous efforts focused on manipulating intracellular metabolic reactions to improve xylose utilization and reduce by-product (e.g., xylitol) accumulation, controlling the xylitol export process might also be a meaningful strategy for reducing its formation and increasing carbon flux toward target products.…”
mentioning
confidence: 99%